Odpowiedzi

2009-12-09T15:16:30+01:00
A)2x+6=20
2x=20-6
2x=14 :2
x=7

b) -4c-46=-2
-4c=-2+46
-4c=44 : -4
c=-11

c) 7x-21=5x
7x-5x=21
2x=21 :2
x=10,5

d) 3c+2=-70
3c=-70-2
3c=-72 :3
c= -24

e) 23+9y=50
9y=27 :9
y=3

f) 13+2x=3
2x=-10 :2
x=-5

g) 6y-13=-52
6y=-39 :6
y=-6,5

h) 33-4x=4x
-8x=-33 :-8
x=4,13

i) 8y-36=24
8y=60 :8
y=7,5

j) -7=5x+1
-5x=8 :-5
x=1,6

k) 4x-4=3
4x=7 :4
x=1,75

j) 5-10x=-2x
-8x=-5 :-8
x=0,62
Najlepsza Odpowiedź!
2009-12-09T15:17:55+01:00
2x+6=20
2x=20-6
2x=14/:2
x=7
-4c-46=-2
-4c=-2+46
-4c=44/:(-4)
c=11

7x-21=5x
-21=5x-7x
-21=-2x/:(-2)
x=10.5

3c+2=-70
3c=-70-2
3c=-72/:3
c=-24

23+9y=50
9y=50-23
9y=27/:9
y=3

13+2x=3
2x=3-13
2x=-10/:2
x=-5

6y-13=-52
6y=-52+13
6y=-39/:6
y= -6.5

33-4x=4x
33=4x+4x
33=8x/:8
x=4.12

8y-36=24
8y=24+36
8y=60
y=7.5

-7=5x+1
-7-1=5x
-8=5x/:5
x=-1.6

4x-4=3
4x=3+4
4x=7/:4
x:1.75

5-10x=-2x
5=-2x+10x
5=8x/:8
x=0.625
2009-12-09T15:27:32+01:00
2x+6=20 |-6
2x=14 |:2
x=7
L= 2*7+6=14+6=20
p= 20

L=P

-4c-46=-2 |+46
-4C=44 |:(-4)
C= (-11)
L= (-4)*(-11)-46= 44-46 = -2
P= -2
L=P

7x-21=5x |-7x
-21= -2x |:(-2)
10,5=x
L= 7*10,5 - 21 = 73,5 -21= 52,5
P= 5*10,5 = 52,5
L=P

3c+2=-70 |-2
3c = -72
c=-24
L= 3*(-24)+2 =-72+2=70
P= 70

23+9y=50 |-23
9y=27 |:9
y=3

13+2x=3 |-13
2x=-10 |:2
x=-5

6y-13=-52 |+13
6y=-39 |:6
y = 6,5

33-4x=4x |+4x
33=8x |:8
4,125=x

8y-36=24|+36
8y = 60 |:8
y=7,5

-7=5x+1 |-1
-8 = 5x |:5
-1,6=y

4x-4=3 |+4
4x=7 |4
x=1,75

5-10x=-2x |+10x
5=8x |:8
0,625=x